VIBRATION MASSAGE CORSET (VMC) UNTUK MEMBANTU PROSES INVOLUSI UTERI PADA IBU POST PARTUM - putri, kirana aulia (Universitas Aisyah Pringsewu, 2023)
Background: Bleeding is one of the causes of increased maternal mortality cases. Post partum bleeding is caused by the failure of uterine involution to contract normally which is commonly referred to as sub-involution. Uterine involution is a process where the uterus and other reproductive organs change to their pre-pregnancy state during the puerperium. This research created an innovative massage girdle as an alternative to uterine involution therapy. Purpose: To prove that the use of Vibration Massage Corset (VMC) together with uterine massage is more effective in helping the process of uterine involution. Methods: Research and Development (RD) type, Quasy Experiment, Pre-Test Post-Test design. The total sample of 32 respondents was divided into 16 control groups which were only given uterine massage, 16 intervention groups were given treatment using VMC and uterine massage. Bivariate analysis using the Wilcoxon and Mann-Whitney test. Results: 14 respondents (87.5%) experienced uterine involution according to the time of involution after using VMC and uterine massage, while the group that was only given uterine massage 11 respondents (68.8%) experienced uterine involution according to the time of involution. The p-value of uterine involution after treatment of the control and intervention groups was 0.024 (p 0.05) so that the use of VMC and uterine massage was more effective in helping the process of uterine involution than just being given uterine massage. Conclusion: Using VMC together with uterine massage is more effective in helping the process of uterine involution than just giving uterine massage.